Disease modeling of ADAMTS9-related nephropathy using kidney organoids reveals its roles in tubular cells and podocytes - Yu, Seyoung; Choi, Yo Jun; Rim, John Hoon; Kim, Hye-Youn; Bekheirnia, Nasim; Swartz, Sarah Jane; Dai, Hongzheng; Gu, Shen Linda; Lee, Soyeon; Nishinakamura, Ryuichi; Hildebrandt, Friedhelm; Bekheirnia, Mir Reza; et al. (Frontiers in Medicine, 2023)
Introduction Mutations in ADAMTS9 cause nephronophthisis-related ciliopathies (NPHP-RC), which are characterized by multiple developmental defects and kidney diseases. Patients with NPHP-RC usually have normal glomeruli and negligible or no proteinuria. Herein, we identified novel compound-heterozygous ADAMTS9 variants in two siblings with NPHP-RC who had glomerular manifestations, including proteinuria. Methods To investigate whether ADAMTS9 dysfunction causes NPHP and glomerulopathy, we differentiated ADAMTS9 knockout human induced pluripotent stem cells (hiPSCs) into kidney organoids. Single-cell RNA sequencing was utilized to elucidate the gene expression profiles from the ADAMTS9 knockout kidney organoids. Results ADAMTS9 knockout had no effect on nephron differentiation; however, it reduced the number of primary cilia, thereby recapitulating renal ciliopathy. Single-cell transcriptomics revealed that podocyte clusters express the highest levels of ADAMTS9, followed by the proximal tubules. Loss of ADAMTS9 increased the activity of multiple signaling pathways, including the Wnt/PCP signaling pathway, in podocyte clusters. Conclusions Mutations in ADMATS9 cause a glomerulotubular nephropathy in kidney and our study provides insights into the functional roles of ADMATS9 in glomeruli and tubules.